Działalność duszpasterska a polityczno-społeczne postawy robotników w Jastrzębiu Zdroju w latach 1980-1981 - Skotnica, Sławomir (Śląskie Studia Historyczno-Teologiczne, 1993)
The years 1980—1981 made the remarkable period in the latest history of Poland. There were two main reasons of that. The first one-it was the explosion of the workers’ protest in August 1980, which embraced industrial plants all over Poland and was terminated by signing of collective agreements between the workers and the communist authorities. They were named after the cities, where they had been signed, namely the agreements of Szczecin, Gdańsk and Jastrzębie. The second reason-it was the foundation, as the result of these protests and agreements, of the Independent Autonomous Trade Union „Solidarity”. The events of 1980—1981 had a great infhience on priests’ activities of the Church in Silesia, especialy in the diocese of Katowice, due to the positively industrial character of the area. In this diocese (presently changed into archdiocese) there is the city of Jastrzębie Zdrój which became the cradle of the coal miners’ strikes in August and September of 1980. The Church in Jastrzębie lavished the priestly attention on the striking coal miners. The priests in aswer to their request crossed the gates of the coal mines. In the coal mines the priests were saying masses, performing the sacrament of penance and reconciliation, corrying on prayers and singing of sacred songs. The priests have already earlier, through their work in the workers environment, created the basis for the striking activities in August, for demanding of justice in the sprit of evangelical love, without using any force. The parish of the Holiest Mary, Mother of Church in Jastrzębie Zdrój. in the years 1980—1981 became a symbol of the activity of people of the Church for the benefit of improving the situation of miners in Silesia. The presbitery of the parish of the Holiest Mary, Mother of Church was the main center of assistance to the strikers, since majority of the miners, working in the coal mines of Jastrzębie and coming from all over Poland, lived within the boundaries of this parish. After the strikes the priests, under the leadership of the parish-priest Czernecki, were meeting the management of IATU „Solidarity” in Jastrzębie, in presence of the bishop Herbert Bednorz, called „the bishop of workers”, due to his great interest in the matters of working people in Silesia. The priests served with help and advise to the trade union activists, introducing to them the social teachings of the Church and facilitating their contacts with representatives of the Catholic lay intellectuals. This beneficial cooperation of the both parties (i.e. the Church and „Solidarity”) was not disturbed even by the conflict within the management of IATU „Solidarity” in Jastrzębie, which took place on the turn of 1980, since the majority fraction proclaiming among others a partnership cooperation with the Church (Stefan Pałka. Tadeusz Jedynak, Ryszard Kuś). has won within the management over the procommunist group lead by the chairman of „Solidarity” in Jastrzębie since 26.01.1981 — Mr. Jarosław Sienkiewicz. The activists of the renewed structures of „Solidarity” in Jastrzębie Zdrój took part in many contacts with the Church in the region and in the country, including international contacts, such as the visit of the „Solidarity” delegation to the pope John Paul II in Vatican. At the end of the article there were shown problems of priests in Jastrzębie Zdrój related to the introduction of the marshal law on the territory of Poland on December 13th, 1981. Since that day the Church in Jastrzębie pined in these specific conditions the activities for the benefit of workers, which depending on circumstances the Church was forced to work inwas more or less connected to the priestly ministrations. The priests visited the strikers and deprived of employment as well as imprisoned miners, bringing them and their families moral consolation and material assistance. The fact that the marshal law did not lead in this area to an agression from the side of the wronged miners towards representatives of the communist authorities, resulted to a great extent from the dependence between the activities of the priests and political and social attitudes of workers in Jastrzębie Zdrój in the years 1980—1981.